Developing Islamic-Based Instructional Materials for Teaching Reading at Islamic Higher Education - Muhsinin Muhsinin; Muhammad Mugni Assapari (Universitas Hamzanwadi, 2023)
This is an educational Research and Development (R and D) aimed at developing Islamic-based reading instructional materials for students of Islamic Education Department. The phases of the research were simplified into three phases: the exploration phase, the model development phase, and the model testing phase. In the exploration phase, an evaluation was conducted to describe the existence and quality of the present reading materials. During the model development phase, a draft of Islamic-based reading instructional materials was designed and revised based on the inputs from FGD and expert evaluators. Try out of the draft model was also conducted in this phase. In the model testing phase, the draft was experimentally tested to see the effectiveness of the product in developing the students’ reading comprehension. This research revealed that the present reading materials did not accommodate the learners needs to learn English using Islamic materials. Therefore, the new reading materials in the forms of Islamic-based reading instructional materials need to be developed. The experimental research proved that the students taught using the designed Islamic-based reading instructional materials performed better in reading comprehension test compared to the students who were taught using the materials taken from the present reading materials. The results of the test indicated that the mean scores of the experimental group were higher than those of the control group. This difference was analyzed statistically using t-test to interpret the difference. The analysis revealed that the Sig. (2-tailed) was .021 which was smaller than the level of significance scores .05 (.012 < .05). This statistically indicated that the different mean scores between the experimental and the control groups were the result of the different treatment given to the two groups. Thus, the use of Islamic-based reading materials influenced the reading comprehension achievement of the students.